The lady at the top of the building - Iris Mónica Vargas (Social Medicine Publication Group, 2020)
When the winds had made full display of their fury, on September 2017, and silence had befallen, a hurricane had only then began its onslaught. It is what happens after, what changes you, and not the roaring of the invisible, wide, spiraling mouth arriving from the sea. Years ago, when I was a little girl, my family and I experienced Hurricane Hugo. We lived then in a small barrio in the mountains of Puerto Rico. Our house was humble as was everything else around us. We didn't have much in the way of economic resources. No common pleasures such as dinning out on Fridays or any other day of the week, no vacation trips to other countries, no fancy schools, no luxuries of any kind. A single gift each Christmas. We lived in a house that my father built all by himself, with wood that soon enough had rotten at the bottom, through which I became acquainted daily with the varied population of insects with whom we shared our surroundings. The structure we called home had one window in the front of the house. Everything else - the entire one bedroom/bathroom the house contained -- was dark. My father worked very hard, changed jobs every few years, and saved money all of his life, diligently, such that one day he could build what would become our next house: a structure made of cement that would take thirty years of work (by all of us), and patience (from all of us), to almost finish. It was that structure, a quarter of it already erected, that would help us survive after hurricane Hugo.